2018
DOI: 10.1016/j.reprotox.2018.07.077
|View full text |Cite|
|
Sign up to set email alerts
|

Peroxisome proliferator activated receptor gamma (PPAR-γ) ligand pioglitazone regulated gene networks in term human primary trophoblast cells

Abstract: Peroxisome proliferator-activated receptor (PPAR-γ) is a nuclear receptor that is highly expressed in placenta. In this study, the PPAR-γ regulated gene networks were characterized in human primary trophoblast cells in vitro. The trophoblasts were isolated from full term placenta after delivery and exposed to 20 μM of the PPAR-γ agonist, pioglitazone, for 72 h and gene expression profiles were examined. Differential expression of selected genes was confirmed with RT-qPCR. Ingenuity pathway analysis was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
(85 reference statements)
1
4
0
Order By: Relevance
“…BCG-induced lipid accumulation [37]. Moreover, stimulation of PPARγ with the ligand pioglitazone in human placental trophoblast cells and goat mammary glands upregulated the transcription levels of fat metabolismrelated genes FABP4 and the perilipin-2 (PLIN2) protein which promotes fat deposition [38]. The results presented in the current study also indicate that exogenous addition of rosiglitazone promotes lipid deposition in STCs, while the addition of GW9662 exerts the opposite effect.…”
Section: Ppar Researchsupporting
confidence: 61%
“…BCG-induced lipid accumulation [37]. Moreover, stimulation of PPARγ with the ligand pioglitazone in human placental trophoblast cells and goat mammary glands upregulated the transcription levels of fat metabolismrelated genes FABP4 and the perilipin-2 (PLIN2) protein which promotes fat deposition [38]. The results presented in the current study also indicate that exogenous addition of rosiglitazone promotes lipid deposition in STCs, while the addition of GW9662 exerts the opposite effect.…”
Section: Ppar Researchsupporting
confidence: 61%
“…These transcription factors belong to the superfamily of nuclear receptors and they are present in a variety of tissues for cellular homeostasis. As PPARs are involved in the development of numerous diseases, such as brain and peripheral inflammation and cancer, and they are considered to be potential molecular targets (30,34,35). Previously, it was shown that PPARγ plays an important role in the regulation of gene expression, such as that of lipoprotein(a), IL-1 and TNF-α (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Pioglitazone improves the endocrine status and causes inhibitory effects on androgen synthesis 12 , and peroxisome proliferator-activated receptor gamma (PPAR-γ) strengthens the effect of insulin and reduces the effects of inflammation by increasing IL-8 and IL-6 13 . Upregulation of several inflammatory and downregulation of noninflammatory genes is associated with failure of IVF 14 .…”
Section: Discussionmentioning
confidence: 99%